Auditing the auditors: the audit oversight board and regulating audit quality in Malaysia - Ismail, Hashanah; Mustapha, Mazlina (David Publishing Company, 2015)
The setting-up of the Malaysian Audit Oversight Board (AOB) in 2010 under the Securities Commission Amendment Act 2010 has extended the role of regulators into the statutory audit domain for public listed companies. Although the auditing profession in Malaysia has International Auditing Standards as prescribed minimum level of quality in the delivery of audit assurance services, self-regulation by the profession alone appears inadequate to ensure the delivery of quality audit services. With co-regulation, auditors now are monitored not just by the profession but also by a new statutory body with considerable regulatory powers to sanction auditors where quality of the audit process has been found wanting. This study solicits the opinions of auditors on their expectations of what the new regulator can achieve. Based on interviews with a sample of 30 auditors, the study finds that the majority believe that audit quality will be taken to a new level following AOB’s remit of registration of auditors, compliance inspection with International Standard on Quality Control (ISQC), monitoring of financial statement quality, and its power of sanctions. A review of AOB’s early years’ inspection confirms these expectations.